2020
DOI: 10.1002/slct.202001195
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chlorinated, Heteroatom‐Rich and Differently Fused Tricyclic β‐Lactams by Cu(I)‐Catalyzed Halogen Atom Transfer Radical Cyclization

Abstract: The application of Cu (I)-catalyzed halogen atom transfer radical cyclization (ATRC) for the synthesis of two different series of chlorinated, heteroatom rich and differently fused tricyclic β-lactams has been demonstrated. N-substituted-3,4dihydropyrimidine-2(1H)-thiones synthesized by Biginelli reaction were used as starting materials for this synthetic pathway which upon S-allylation/alkylation furnished 2-allylthio/alkylthio-1,4-dihydropyrimidines (cyclic imines). Staudinger reaction of these cyclic imines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A Cu-catalyzed radical reaction of allyl bicyclic β -lactam for the synthesis of tricyclic β -lactams has been reported by Dawra and coworkers in 2020. The reaction of allyl bicyclic β -lactam 125 under the catalysis of CuCl/PMDETA in DCE at room temperature gave products 126 or 127 in good to excellent yields ( Scheme 31 ) [ 57 ]. Between two alkenyl groups ( S -allyl and N -allyl) the competitive experiments revealed that the ATRC is more favorable to the S -allyl group than the N -allyl group.…”
Section: Second Functionalization With X Via Atom-transfer Radical Cy...mentioning
confidence: 99%
“…A Cu-catalyzed radical reaction of allyl bicyclic β -lactam for the synthesis of tricyclic β -lactams has been reported by Dawra and coworkers in 2020. The reaction of allyl bicyclic β -lactam 125 under the catalysis of CuCl/PMDETA in DCE at room temperature gave products 126 or 127 in good to excellent yields ( Scheme 31 ) [ 57 ]. Between two alkenyl groups ( S -allyl and N -allyl) the competitive experiments revealed that the ATRC is more favorable to the S -allyl group than the N -allyl group.…”
Section: Second Functionalization With X Via Atom-transfer Radical Cy...mentioning
confidence: 99%